Preliminary evidence of an association between the functional c-kit rs6554199 polymorphism and achalasia in a Turkish population - EREN, FATİH; ATUĞ, ÖZLEN; ÖZEN ALAHDAB, YEŞİM; YILMAZ, YUSUF (WILEY, 2012)
Background C-kit-positive interstitial cells of Cajal (ICC) of the lower esophageal sphincter are reduced in achalasia. Two functional gene polymorphisms (rs2237025 and rs6554199) within the c-kit gene may affect its transcriptional activity. In this pilot study, we hypothesized that these polymorphisms would be associated with achalasia. Methods Genomic DNA was extracted and real-time PCR reactions were used to determine the rs2237025 and rs6554199 c-kit polymorphisms in 88 Turkish patients with achalasia and 101 healthy controls. Key Results The frequency of the T allele of rs6554199 was significantly higher in patients with achalasia [odds ratio (OR): 1.55; 95% confidence interval (CI), 1.03-2.34; P = 0.038] compared with the G allele. Under a dominant model of inheritance, the carriage of at least one T allele was significantly more frequent in patients with achalasia (80.7%) than in controls (65.3%; OR: 2.21; 95% CI, 1.13-4.33; P = 0.022). No association of the c-kit rs2237025 polymorphism with achalasia was detected. Conclusions & Inferences Despite the small sample size and the possibility of a false positive finding, our preliminary data support the hypothesis that the T allele of the c-kit rs6554199 polymorphism may be associated with achalasia in the Turkish population. These findings need to be replicated in other racial-ethnically diverse populations.
Keywords: achalasia; association study; c-kit; polymorphism; STEM-CELL FACTOR; INTERSTITIAL-CELLS; CAJAL; DENSITY; DISEASE